The Effect of Different Seed Cutting Treatments and Concentrations of BAP for the Successful In Vitro Micrografting of Mangosteen (Garcinia mangostana L.) - Agustina, Mira; Maisura, Maisura; Handayani, Rd. Selvy (Yayasan Pertanian Tropika Indonesia (YPTI), 2020)
The efforts of the rooting of regenerants resulting from gamma-ray irradiation require plant tissue culture, which known as micrografting. This technique can help irradiated regenerants to develop a well root system, by combining non-rooting shoots with rooted in vitro cultured shoots of plant rootstock. The purpose of this study was to examine the effect of seed explants cutting and the application of different BAP concentrations for the successful micro-grafting of mangosteen in vitro. This experiment employed Complete Randomized Design (CRD) Factorial with two factors and ten replications. The first factor was the cutting treatments of mangosteen seeds explants for rootstock shoots, consisting of 2 types of seeds: uncut and cut seeds. The second factor was BAP concentrations: BAP 0 mg/l and BAP 2 mg/l. The results showed that the division of the seeds had an influence on the results of micro-grafting mangosteen in vitro. Micrografted mangosteen, which rootstock applied from undivided seeds, possessed faster growth, longer shoots, and produce more leaves compared to rootstock shoots from the divided seeds. BAP concentrations also contributed to the results. The application of BAP 2 mg/ demonstrated better effect on all variables observed. There were no interactions between seed divisions and BAP concentrations in all observed variables.